Institutional sources of legitimacy for international organisations: Beyond procedure versus performance - Dellmuth, Lisa Maria; Scholte, Jan Aart; Tallberg, Jonas (Review of international studies, 2019)
This article addresses a significant gap in the literature on legitimacy in global governance, exploring whether, in what ways, and to what extent institutional qualities of international organisations (IOs) matter for popular legitimacy beliefs towards these bodies. The study assesses the causal significance of procedure and performance as sources of legitimacy, unpacks these dimensions into specific institutional qualities, and offers a comparative analysis across IOs in three issue areas of global governance. Theoretically, the article disaggregates institutional sources of legitimacy to consider democratic, technocratic, and fair qualities of procedure and performance. Empirically, it examines the effects of these institutional qualities through a population-based survey experiment in four countries in different world regions with respect to IOs in economic, security, and climate governance. The findings demonstrate that both procedure- and performance-related aspects of IO policymaking matter for popular legitimacy beliefs. This result holds across democratic, technocratic, and fair qualities of IO procedure and performance. Disaggregating the results by issue area indicates that a broader scope of institutional qualities are important for legitimacy beliefs in economic governance compared to security governance and, especially, climate governance. These findings suggest that propositions to reduce the institutional sources of IO legitimacy to single specific qualities would be misguided.